2018
DOI: 10.1182/bloodadvances.2017015602
|View full text |Cite
|
Sign up to set email alerts
|

Selectins and chemokines use shared and distinct signals to activate β2 integrins in neutrophils

Abstract: Key Points Selectin and chemokine signals use both Rap1a and PIP5Kγ90 to activate β2 integrins in neutrophils. Suboptimal chemokine signals synergize with selectin signals to activate β2 integrins in neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 58 publications
1
57
0
Order By: Relevance
“…54 neutrophils mediate both adhesion and signaling. 3,26,42,55 Oligomeric or immobilized P-selectin or anti-PSGL-1 antibodies can induce signals in the absence of shear stress. 56,57 Force-dependent interactions under shear stress might amplify signaling by increasing the number of P-selectin/PSGL-1 bonds or by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 neutrophils mediate both adhesion and signaling. 3,26,42,55 Oligomeric or immobilized P-selectin or anti-PSGL-1 antibodies can induce signals in the absence of shear stress. 56,57 Force-dependent interactions under shear stress might amplify signaling by increasing the number of P-selectin/PSGL-1 bonds or by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were isolated from bone marrow leukocytes by a density gradient method. 26 Isolation of mouse lung endothelial cells (MLECs) was performed as described previously, 27,28 with minor modifications. Briefly, lungs from 2 or 3 mice were washed, minced into 1-to 2-mm 2 pieces in 10% fetal bovine serum (FBS)-Dulbecco's modified Eagle medium (DMEM) with antibiotics, and digested with collagenase type I (2 mg/mL) at 37°C for 1 hour with occasional vortex.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the same study both Talin and Kindlin-3 were reported as essential to confer a high affinity state and migration arrest to to binding of ICAM. More recently, Yago and co-workers reported that chemokine signaling also activated both PIP5Kγ90 (phosphatidylinositol-4-phosphate 5-kinase γ90) and PI3Kγ dependent signaling which cooperated with Rap-1 to achieve an intermediate state of affinity of LFA-1 [37]. In addition, binding of PSGL-1 (P-selectin glycoprotein ligand-1) to selectins as expressed by endothelial cells activated Rap-1 and PIP5Kγ90 signaling via Src kinases as well.…”
Section: Activation Of β2 Integrinsmentioning
confidence: 99%
“…G protein–coupled receptors on rolling neutrophils bind chemokines presented on the apical endothelium, leading to “inside-out” signals that induce conformational changes of β2-integrins ( 39 ), mediating slow rolling (low concentration) and arrest (high concentration). Chemokines synergize with selectins to activate β2-integrins when chemokine availability is limited ( 40 ). Engagement of endothelial P- or E-selectin with neutrophilic PSGL-1 triggers signals that separate LFA-1 α and β cytoplasmic tails ( 41 ), which induces integrin extension from the bent to an extended intermediate-affinity conformation ( 42 ).…”
Section: The Leukocyte Recruitment Cascade: a Paradigm Established Inmentioning
confidence: 99%